MENUJU DASAR-DASAR BARU FIKIH ISLAM: : Kajian Konseptual Ilmu Fikih - Bashori Alwi (Fakultas Syariah - IAI Al-Qolam Malang, 2021)
Fiqh is a major need in Islam, therefore it must be able to become a problem solver in the problems of the umat, Fiqh must be relative and flexible, so that it can be used by Muslims wherever they live. To be taqlid to previous madhhab scholars is a necessity, but reforms in relevant Islamic thought are eagerly awaited by the people of this modern era, especially in this digital era. So that people can continue to carry out their activities according to the provisions of the Shari'a that have been outlined by the Prophet Muhammad. The most important formulation in the renewal of Islamic law is not to deviate or contradict the provisions of the texts, 2). Provide benefits for the ummah and avoid harm, 3). It really comes from the results of common sense of thinking, which has a general standard of truth, not because of any particular interest that drives it.